155 Histopathological Study of 62 Sudden Cardiac Death Victims with Isolated Mitral Valve Prolapse. (3rd June 2016) - Steriotis, Alexandros; Krexi, Lydia; Plonczak, Agata; Finocchiaro, Gherardo; Papadakis, Michael; Sharma, Sanjay; Sheppard, Mary
Abstract : The aim of the study was to evaluate the cardiac histopathological findings of sudden cardiac death victims with isolated mitral valve prolapse. We studied 62 sudden cardiac death victims with isolated mitral valve prolapse that represented 1.7% of our total sudden cardiac death cohort. The heart was examined macroscopically and microscopically. Toxicology results were negative. The series included 33 males and 29 females (mean age 37 ± 14 years). In all cases the mitral valve exhibited degenerative changes of bileaflet thickening, stretching and prolapse of the leaflets in to the left atrium. The left ventricle showed no evidence of fibrosis macroscopically, but in 46 (74%) of cases myocardial fibrosis was detected with histology. The majority of the sudden cardiac death victims with myocardial fibrosis had involvement of both papillary muscles and the adjacent myocardial wall (30 cases, 65%), while in the remaining it was localised to one papillary muscle and the adjacent wall. The posteromedial papillary muscle and posteroinferior wall were involved in the majority (42 cases, 91%). The involvement of the left ventricular wall was always subendocardial and/or midmural and the type of fibrosis was replacement type and/or interstitial. In conclusion, the majority of sudden cardiac death with isolated mitral valve prolapse exhibits a bileaflet mitral valve prolapse with localised fibrosis, involving one or both papillary muscles and the adjacent subendocardial layer of the left ventricular wall. This myocardial fibrosis can provide a substrate for ventricular arrhythmias and sudden cardiac death. However 26% of the sudden cardiac death victims had histologically normal heart so other mechanisms to explain the sudden death must be considered.